Comparative Study of Widal and Typhidot Test in the Diagnosis of Typhoid Fever in Children - Sreenivasa, B.; Kumar, G.V. (Journal of Nepal Paediatric Society, 2016)
Introduction: Typhoid fever is a life threatening systemic infection that is usually presented with non- specific symptoms and signs. Its diagnosis is usually confirmed by blood culture and Widal test. The delayed results of microbiologic examination and the unreliable results of Widal test makes the search for a rapid and reliable method for diagnosis of typhoid fever. An early and accurate diagnosis is necessary for a prompt and effective treatment. The objectives were to compare the sensitivity and specificity of Widal test and typhidot with the blood culture in the diagnosis of typhoid fever in children. Material and Methods: A total of 200 hundred clinically suspected typhoid fever cases of 2-12 year age groups from both sexes attending Basaveshwara Medical College Hospital Chitradurga were studied. The blood collected aseptically was used for blood culture and clotted blood was used for Widal test and typhidot test. Results: Of 200 blood samples studied, 28 cases were positive by blood culture. Widal test showed sensitivity and specificity of 53% and 83% on blood culture proven cases. Typhidot test showed sensitivity and specificity of 93% and 83%, respectively on blood culture proven cases. Conclusion: Using blood culture as the gold standard, typhidot showed a higher sensitivity compared to Widal test. The specificity of both Widal and typhidot remained the same. Typhidot could be a practical alternative to Widal test in the diagnosis of typhoid fever even in the resource poor laboratories. J Nepal Paediatr Soc 2016;36(2):131-135.